2011
DOI: 10.1088/0957-4484/22/28/285303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrons on the shape of nanopores prepared by focused electron beam induced etching

Abstract: The fabrication of nanometric pores with controlled size is important for applications such as single molecule detection. We have recently suggested the use of focused electron beam induced etching (FEBIE) for the preparation of such nanopores in silicon nitride membranes. The use of a scanning probe microscope as the electron beam source makes this technique comparably accessible, opening the way to widespread fabrication of nanopores. Since the shape of the nanopores is critically important for their perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
(77 reference statements)
1
12
0
Order By: Relevance
“…3(a-h)). Sample applications include iterative editing of individual nanostructures [85,19], repair of photolithographic masks [27,28], fabrication of nanopores in membranes [30,35], etching of 3D in-plane features in photoresist [37], and re-shaping of tips used in scanning probe microscopy [33,38]. EBIE has also been used to improve the purity of materials grown by EBID.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(a-h)). Sample applications include iterative editing of individual nanostructures [85,19], repair of photolithographic masks [27,28], fabrication of nanopores in membranes [30,35], etching of 3D in-plane features in photoresist [37], and re-shaping of tips used in scanning probe microscopy [33,38]. EBIE has also been used to improve the purity of materials grown by EBID.…”
Section: Applicationsmentioning
confidence: 99%
“…The technique is analogous to focused ion beam processing [6][7][8][9][10][11], but avoids damage, staining and redeposition artifacts caused by ion bombardment. EBIE is realized using gaseous precursors such as H 2 O, O 2 , NH 3 , XeF 2 , Cl 2 and SF 6 , which have been used to volatilize a wide range of materials, including graphene [12], single [13] and multi-walled [14] C nanotubes, amorphous carbon [15][16][17][18], single crystal [19][20][21][22] and nano-crystalline [23] diamond, Si, SiO 2 , Si 3 N 4 , Cr, Ti, TaN and photoresist [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Historical overviews and reviews of the EBIE technique and the underlying chemical pathways can be found in references [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in nanofabrication techniques allow artificial solid-state nanopores to be fabricated in Si 3 N 4 , SiO 2 , Si, and alumina [2,6,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. These nanopore devices uncover many advantages, such as the ability to control a pore diameter, increased mechanical strength, and integration with micro/nano-devices.…”
Section: Introductionmentioning
confidence: 99%
“…To date, inductively-coupled plasma (ICP)-enhanced reactive ion etching (RIE) [13,17,21,22], focused ion beam (FIB) micromachining via transmission electron microscopy (TEM) technology [6,13,14,17,20,22,25], and electron beam lithography [2,12,18,20] have been used frequently to pattern micro and nanopores directly on the substrate after some modification. Despite the availability of large varieties in pore fabrication techniques, it is still very desirable to develop simpler and faster methods without using the above mentioned high energy electron beam techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation